The Financing of Ideas and the Great Deviation - Garcia-Macia, Daniel (IMF Working Papers; Working Paper ;, 2017)
Why did the Great Recession lead to such a slow recovery? I build a model where heterogeneous firms invest in physical and intangible capital, and can default on their debt. In case of default, intangible assets are harder to seize by creditors. Hence, intangible capital faces higher financing costs. This differential is exacerbated in a financial crisis, when default is more likely and aggregate risk bears a higher premium. The resulting fall in intangible investment amplifies the crisis, and gradual intangible spillovers to other firms contribute to its persistence. Using panel data on Spanish manufacturing firms, I estimate the model matching firm-level moments regarding intangibles and financing. The model captures the extent and components of the Great Recession in Spanish manufacturing, whereas a standard model without endogenous intangible investment would miss more than half of the GDP fall. A policy of transfers conditional on firm age could speed up the recovery, as young firms tend to be more financially constrained, particularly regarding intangible investment. Conditioning transfers on firm size or subsidizing credit (as in current E.U. policy) appears to be less effective.